PENGENDALIAN PERSEDIAAN MATERIAL PLASTIK JENIS POLYETHYLENE TEREPHTHALATE (PET) DENGAN METODE ECONOMICAL ORDER QUANTITY (EOQ) PROBABILISTIK (Studi Kasus : PT. Penjalindo Nusantara) - zahrah, Zahrah Fadhilah; Imas Widowati; Elly Setiadewi (Jurnal Teknologika, 2023)
Penjalindo Nusantara which is a company engaged in printing or printing, especially packaging or packaging printing. In the process of purchasing materials at PT. Penjalindo Nusantara has problems with late delivery of materials from Vendors, which affects the production process. Based on these problems, it is necessary to conduct research on inventory control using the Probabilistic Economic Order Quantity (EOQ) method. The results of the research analysis using the Probabilistic Economic Oder Quantity (EOQ) method show that the company can place an optimal order of 6330 kg for each order with a safety stock of 325 kg, the company makes a Reorder Point when inventory reached 3055 kg.